Ready, Set, Communicate: Measuring Usability of Instructional Modules Designed to Improve Communications Skills of Students Studying Agricultural Sciences - Theresa Pesl Murphrey; Audra W. Richburg; Holli R Leggette; Shannon L. Norris-Parish; Jean A Parrella (Journal of Applied Communications, 2023)
Well-developed communications skills are essential to a proficient agricultural workforce. Online instruction via reusable learning modules (RLMs) is one way agricultural science faculty can provide their students with expert communications skills training. Although RLMs have many benefits, their value degrades rapidly if the learner cannot access or use the technology efficiently. Therefore, online instruction must be tested to ensure usability. The purpose of our study was to assess the usability of RLMs developed to bolster the communications skills of students studying in the agricultural sciences and provide guidance for future curricula and online instruction development. We used quantitative and qualitative data sources to assess the usability of three RLMs, according to N = 21 students. The usability metrics we assessed included learnability, navigation, video function, document access and readability, quiz and assignment practicality, and task difficulty. The RLMs garnered high usability scores from participants who had positive impressions and experiences completing them. Participants demonstrated an increase in confidence to perform communications skills and an increase in knowledge about communications after completing the modules. They thought embedded videos, documents, quizzes, and assignments were helpful in learning communications concepts. Some recommended improving navigation, document readability, and assignment details. Based on our findings, we recommend RLM developers embed short videos, printable handouts, and quizzes into RLMs, and include an overview of documents’ key points to guide reading. Participants’ positive feedback and willingness to engage with the RLMs suggests incorporating the RLMs into agricultural science courses will help students develop into science communicators.
Keywords: instructional design; online learning; reusable learning modules; science communications